Implementation of Pancasila Management Principles in Junior High Schools in Indonesia - Ade Sopyan Hadi; Joseph Andhika Leonardo Rahail (Educare : Jurnal Penelitian Pendidikan dan Pembelajaran, 2026)
Indonesia is a country that adheres to the Pancasila ideology, starting from the importance of implementing Pancasila values in state life including in the field of education. However, in practice, school management is often still oriented solely to administrative aspects without being balanced by the application of Pancasila values in school management. The approach used in this study is a qualitative approach. In this study the type of research applied is a literature study. The results of this study show data that the meeting to design the Pancasila Student Profile Strengthening Project activities at MTsN 7 Jakarta is part of the planning, the Pancasila Student Profile Strengthening training by the Bireun Regency Education and Culture Office is part of the organization, the celebration of the Pancasila Student Profile Strengthening Project by students of SMPN 1 Purwakarta is part of the implementation of management. The discussion of this study, namely planning, organizing, and implementation in the Pancasila Student Profile Strengthening Project Program, shows a systematic effort in internalizing Pancasila values. Thus, in practice, these three management aspects still require strengthening in terms of substance, sustainability, and critical evaluation to truly produce an authentic Pancasila Student Profile, not simply an administrative achievement within the Merdeka Curriculum framework. Based on the research results, it can be concluded that the implementation of Pancasila management principles has been systematically implemented.